EKSISTENSI SENI TARI KREASI MODERN DALAM MENGEMBANGKAN NILAI KARAKTER OLEH KAMPUS MENGAJAR 7 DI SDN 22 AMPENAN - Maulani Nurasri Ananda; Anjani, Nurvita Dwi (Institut Agma Islam Hamzanwadi NW Lombok TImur, 2024)
Abstract : Dance is a form of regional culture that contains many cultural values ​​that are strong in social, cultural, philosophical and spiritual values. The cultural values ​​of each dance movement are able to describe the identity of a region. Students' personalities in character building through dance have the aim of being a form of existence in learning traditional dance at school in forming a learning process that is fun, creative, communicative and aesthetic (Ayu Retnoningsih, 2017). However, over time, traditional dance has faded with western culture, so the existence of character strengthening has had a decreasing impact. The development of the times coupled with technological developments seems to be eroding various local wisdom values, especially for the younger generation and children (Umi Mahmudah1 et al., n.d.). Therefore, the author wants to provide efforts to prevent the erosion of traditional culture and western culture by preserving dance movements and instilling character from elementary school age, especially at SDN 22 Ampenan. This research uses descriptive qualitative analysis. The research results were obtained through observation, interviews and documentation. With this dance training, it is hoped that it can preserve culture and also foster students' character of cooperation, tolerance, discipline, national spirit, love of the country, and responsibility. Key Word : Dance, Character Values, Teaching Campus